2022
DOI: 10.21037/tgh.2020.03.03
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the pre-malignant stomach: from guidelines to practice

Abstract: Gastric adenocarcinoma develops after stepwise progression from normal mucosa through to adenocarcinoma most commonly after being triggered by Helicobacter pylori (H. pylori) infection. As disease is often diagnosed late, the prognosis for gastric adenocarcinoma is poor. Identifying pre-malignant mucosal lesions such as atrophic gastritis, intestinal metaplasia and dysplasia is one strategy adopted by clinicians to reduce cancer related mortality. Surveillance of high-risk individuals and endoscopic resection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 107 publications
0
2
0
Order By: Relevance
“…In our study, precursor lesions of GC, such as AG and IM, were observed by histology in 45.0% of adults; the frequencies in Western populations vary between 0% and 8%, whereas in areas of high incidence of H. pylori , the frequency varies between 33% and 84% [ 4 ]. Consistent with this, we observed H. pylori infection in 41.3% of the adults in our population.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, precursor lesions of GC, such as AG and IM, were observed by histology in 45.0% of adults; the frequencies in Western populations vary between 0% and 8%, whereas in areas of high incidence of H. pylori , the frequency varies between 33% and 84% [ 4 ]. Consistent with this, we observed H. pylori infection in 41.3% of the adults in our population.…”
Section: Discussionmentioning
confidence: 99%
“…However, the presence of antral intestinal metaplasia in one rat out of six (17%) at 24 postoperative weeks may alert us to the potential long-term consequences of SG on the gastric mucosa. Indeed, intestinal metaplasia is considered a pre-malignant lesion of gastric cancer in humans [30,31]. The second limitation is the absence of a reflux study by esophageal pH monitoring because this procedure is difficult to perform and not reproducible in rodents.…”
Section: Discussionmentioning
confidence: 99%